Chorebus (Phaenolexis) nigriridis TOBIAS 1998 - Papp, J. (Zenodo, 2007)
Chorebus (Phaenolexis) nigriridis TOBIAS, 1998 – 1 ♀: KU 23 (27 V 1993). – Known in Asiatic Russia (Sakhalin) and Mongolia (PAPP 2005: 227). New to the fauna of Korea. Published as part of Papp, J., 2007, Braconidae (Hymenoptera) From Korea Xxii. Subfamily Alysiinae, pp. 1-38 in Acta Zoologica Academiae Scientiarum Hungaricae 53 (1) on page 9, DOI: 10.5281/zenodo.5731826